Liberalization in Formulating Policy of Urban and Regional Planning A Study on the Function Change of the Farming Area of Surakarta City Suburban, A Politic-Economics Perspective Review. - Budiman Widodo & Winarti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Environmental and food issue have recently been an international concern in whichboth of them have been signed by the increased price of international food. Alsofood issue cannot be separated from land availability as a primary productionfactor. Farming land in Indonesia is already adequate, the problem, however, lieson the narrowing potential farming land due to its land conversion to non-farmingand the absence of commitment and regulation which are capable of protectingfarming land, a country’s commitment toward food security is actually an indicatorof a country regarding food issue. Really farming land to use non agricurtural asbissnies and property priorites.This research aims to describe, analysis and interpret 1) liberalization occurrence ofregional lay out policy, 2) government’s role and other participants in the makingprocess of urban regional planning policy in suburban area of Surakarta city, 3)Community protest against regional and urban planning policy in suburban areas ofSurakarta city, 4) a model of policy of regional and urban planning or construction,a theory of reconstruction of regional and urban planning policy in suburban areasof Surakarta city.KeyWords: Liberalization, Conversion, Role Actor